2002
DOI: 10.1177/002215540205000906
|View full text |Cite
|
Sign up to set email alerts
|

CD9 Expression in Solid Non-neuroepithelial Tumors and Infiltrative Astrocytic Tumors

Abstract: The tetraspan membrane protein CD9 is normally expressed in the mature myelin sheath and is believed to suppress the metastatic potential of certain human tumors. In this study we identified CD9 in a variety of brain tumors by immunohistochemical (IHC) and immunoblotting analyses. We examined 96 tumor samples and three glioma cell lines in addition to a murine brain tumor model of transplanted glioma cells in CD9-deficient mice and control mice. CD9 was expressed not only in solid non-neuroepithelial tumors bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
4
10
0
1
Order By: Relevance
“…2a). In contrast, expression of CD9 in human cerebral white matter was higher than in glioma cell lines A172 (p = 0.003) and U343MG (p = 0.004), presumably reflecting high amounts of CD9 localized mainly along the outermost membrane of compact myelin [20] (Fig. 2a).…”
Section: Cd9 Is Expressed In Glioma Cell Lines and Glioblastoma Specimentioning
confidence: 88%
“…2a). In contrast, expression of CD9 in human cerebral white matter was higher than in glioma cell lines A172 (p = 0.003) and U343MG (p = 0.004), presumably reflecting high amounts of CD9 localized mainly along the outermost membrane of compact myelin [20] (Fig. 2a).…”
Section: Cd9 Is Expressed In Glioma Cell Lines and Glioblastoma Specimentioning
confidence: 88%
“…However, there are two investigations in the literature describing both the cytoplasmic and membranous patterns, as noted in our study in addition to the usual membranous staining. The first was by Kawashima et al (2002) and the second was by Houle et al (2002)). In the former, CD9 expression was evaluated in different types of brain tumours, and they concluded that CD9 expression in astrocytic tumours correlated with their malignancy and thus CD9 protein may have a different role in brain tumours than solid tumours elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CD9 overexpression has been reported in aggressive gastric carcinomas (Hori et al, 2004) and high-grade astrocytic tumors (Kawashima et al, 2002). Therefore, CD9 could be required for the invasive growth of TGCTs.…”
Section: Role Of Ddx1 In Testicular Tumorigenesismentioning
confidence: 99%